1992
DOI: 10.1063/1.106681
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum wire and dot formation by chemical vapor deposition and molecular layer deposition of one-dimensional conjugated polymer

Abstract: Interference rings formation inside cellulose from a back-reflected femtosecond laser pulse J. Appl. Phys. 112, 066101 (2012) Anisotropic optical absorption of organic rubrene single nanoplates and thin films studied by μ-mapping absorption spectroscopy Appl. Phys. Lett. 101, 113103 (2012) Raman and low temperature photoluminescence spectroscopy of polymer disorder in bulk heterojunction solar cell films APL: Org. Electron. Photonics 5, 185 (2012) Raman and low temperature photoluminescence spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 4 publications
2
51
0
Order By: Relevance
“…This is consistent with work by Yoshimura et al, 20 who found in optical measurements an absorption peak energy of 4.9 eV for TDA and and 2.9 eV for a copolymer of TDA and DAB. From ab initio calculations, Onipko et al found a gap value of 5 eV for 4-ATP and 4.1 eV for ATD.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with work by Yoshimura et al, 20 who found in optical measurements an absorption peak energy of 4.9 eV for TDA and and 2.9 eV for a copolymer of TDA and DAB. From ab initio calculations, Onipko et al found a gap value of 5 eV for 4-ATP and 4.1 eV for ATD.…”
Section: Discussionsupporting
confidence: 82%
“…Traditionally, ALD has been used to fabricate rather simple well-known inorganic materials, such as binary oxides and nitrides. The range of materials was fundamentally broadened by experiments producing organic polymers in the 1990s by a variant of ALD, now commonly known as molecular layer deposition (MLD), named after the molecular layer-by-layer fashion the film grows during the deposition [59]. Then – most excitingly – in the late 2000s the two techniques, ALD and MLD, were combined to produce inorganic–organic hybrid materials (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One of the tailored nanoscale structures constructed by MLD is the organic MQDs such as polymer MQDs [5,14,32] and molecular MQDs [8,20]. The polymer MQDs are polymer wires containing quantum dots, and the molecular MQDs are molecular wires containing quantum dots.…”
Section: Organic Multiple Quantum Dots (Mqds)mentioning
confidence: 99%
“…As shown in Figure 8.11, the absorption peak shifts toward the higher energy side in the order of poly-AM quantum wire, OTPTPT, OTPT, and OT, namely, with decreasing the quantum dot length. The peak positions are plotted by squares in The quantum-dot-length dependence of the absorption peak position, which was derived from the quantum-confined electron model, is also presented in Figure 8.12 by a dotted line [5]. The calculation was carried out using the following expression for the energy of electrons confined in a quantum dot with infinite potential barrier heights:…”
Section: Quantum Confinement Effect In Polymer Mqdsmentioning
confidence: 99%